Palliative Care Patients' Quality of Dying and Circumstances of Death—Comparison of Informal Caregivers' and Health-Care Professionals' Estimates. (July 2018) - Stiel, Stephanie; Heckel, Maria; Wendt, Kim Nikola; Weber, Martin; Ostgathe, Christoph
Background: Patient-reported outcomes are usually considered to be the gold standard assessment. However, for the assessment of quality of dying and death, ratings of informal caregivers (ICGs) or health-care professionals (HCPs) must be considered for ethical and methodological reasons. This article aims to present results of ICGs' and HCPs' estimates of the questionnaire, quality of dying and death (QoDD) on patients who died in PCUs and to compare the level of agreement of both ratings/raters. Methods: The parent validation study to this analysis assessed the ICG and HCP versions of the QoDD. Descriptive statistics are presented for each item in both versions. T tests for the estimation of differences between ICG and HCP were performed. Case-related absolute differences between estimates were analyzed regarding the extent of agreement and deviation. Results: Two hundred fifteen matched ICG and HCP ratings were analyzed. The ratings in all 6 QoDD dimensions were high; single items scored low. Mean absolute difference between both ratings was 0.33 (standard deviation [SD]: 3.08; median 0.05) on a 0 to 10 numerical rating scale and ranges between −8.24 (higher rating of ICGs compared to HCPs) and 9.33 (higher rating of HCPs compared to ICGs). Conclusions: The findings appear to show a high satisfaction with quality of dying and death as rated by ICGs and HCPs, but we suspect this might be indicative of a methodological challenge, that is, a ceiling effect in both assessments. Single low scoring items may provide important clues for improvement in end-of-life care. Although descriptive data show comparable mean values and standard deviations, the actual congruence of ratings is low. In summary, replacing one rating by another cannot be recommended.